Energy extraction from marine currents in the Guadiana estuary. Preliminary results - Calero Quesada, María Concepción; García Lafuente, Jesús Manuel; Delgado-Cabello, Javier; Moreno Navas, Juan (Universidad de Vigo, 2018)
A hydrodynamic model of the Guadiana Estuary has been used to study the energy extraction from marine currents. The Guadiana Estuary (SW of Iberian Peninsula) is a mesotidal estuary dominated by the tide. The strongest marine currents are located in the mouth at superficial layer where the energy flux is about 900 W/m2 during spring tides. In addition to the mean energy flux, other characteristics of the flow, such as permanence, direction of the currents or vertical shear, have been taken into account to complete the study the suitability of the area. In an estuary dominated by the tide, asymmetries are important because flood tide and ebb tide have different durations. In the Guadiana Estuary, although the ebb tide is larger than the flood tide is possible to obtain energy in both cases. However, it could be necessary to consider the difference in duration between flood and ebb tide in the characteristics of the flux to decide the most suitable energy extraction device.
Keywords: Estuarios - Congresos; Mareas - Congresos; Guadiana Estuary; Energy flux; Hydrodynamic model; Suitability